(untitled) (Tempo e Argumento, 2022)
Since before Brazil’s independence, the figure of the "Brasileiro" has occupied an important place in Portuguese literature, fictional and non-fictional. And the qualification has always entailed the idea of an intermediate nature between two worlds. In the space of the Atlantic monarchy there were no Portuguese and Brazilians, but there were very distinct territories, and the name "Brasileiro" meant the Portuguese who went to live in Brazil and then returned, or not, to the kingdom. In the 19th century, the maintenance and renewal of this migratory circuit was consolidated in a post-colonial international context between two independent countries. Especially in the second half of the century, the significant increase in the flow of people was reflected in the increased presence of the "Brasileiro" in literary representations, in the debates of public opinion and even in political agendas. But in this context, and considering the colonial past that united Portugal and Brazil, the "Brasileiro" was not seen as a mere emigrant. But, in fact, as a figure who continued to mediate between two worlds, between two national entities, without ever corresponding to the integrity of either origin or destination: a hybrid social category and, we shall see, a transnational one. Keywords: Portugal; Brazil; transnationalism; emigration; national identity; social categorization.